PELAKSANAAN PERJANJIAN EKSPEDISI MELALUI ANGKUTAN UDARA (Sudi pada PT Anugerah Semesta Persada) - RIO PERANATA SEBAYANG (PREMISE LAW JURNAL, 2016)
Shipping agreement with PT Anugerah Semesta Persada was made verbally. PT Anugerah Semesta Persada used verbal agreement because not only it acted on behalf of the consigner, but also as the expediter that directly connected with the shipping agency. It was the accountability of PT Anugerah Semesta Persada that the customer incurred loss in the shipping agreement because of the very limited availability of air freight transportation. PT Anugerah Semesta Persada was accountable for the compensation due to its fault to pay the highest price of the goods. It had not paid the compensation for the transport cost that had been expended by the consigner .The legal protection for the consumers that incur loss in the goods shipping agreement with PT Anugerah Semesta Persada is regulated in the legal provisions regarding freightage either preventively or repressively. Keywords: Inheritance Distribution, Reconciliation Deed, Legal Force